In-silico molecular design of heterocyclic benzimidazole scaffolds as prospective anticancer agents - Tahlan, Sumit (BMC Chem, 2019)
Benzimidazole is a valuable pharmacophore in the field of medicinal chemistry and exhibit wide spectrum of biological activity. Molecular docking technique is routinely used in modern drug discovery for understanding the drug-receptor interaction. The selected data set of synthesized benzimidazole compounds was evaluated for its in vitro anticancer activity against cancer cell lines (HCT116 and MCF7) by sulforhodamine B (SRB) assay. Further, molecular docking study of data set was carried out by Schrodinger-Maestro v11.5 using CDK-8 (PDB code: 5FGK) and ER-alpha (PDB code: 3ERT) as possible target for anticancer activity. Molecular docking results demonstrated that compounds 12, 16, N9, W20 and Z24 displayed good docking score with better interaction within crucial amino acids and corelate to their anticancer results. ADME results indicated that compounds 16, N9 and W20 have significant results within the close agreement of the Lipinski’s rule of five and Qikprop rule within the range and these compounds may be taken as lead molecules for the discovery of new anticancer agents. [Image: see text]